Religiositas Lansia Muslim di UPTD Griya Werdha Surabaya - Triana Rosalina Noor (Universitas Islam Tribakti Lirboyo Kediri, 2021)
This research aims to describe the religiosity of the elderly as seen from aspects of beliefs, rituals, knowledge, experience, and practice. This research was conducted in UPTD Griya Werdha Surabaya using a qualitative approach to phenomenology study as type. Retrieval data used in-depth interview techniques, observation, and documents five elderly Muslims using a purposive technique. The result of the research indicates that the spiritual dimension of the elderly has increased since in UPTD Griya Werdha Surabaya. The elderly forced their belief by carrying out religious rituals taught before and improved the quality to be better as they are now. Religious obtained through religious activities provided by the Griya Werdha through spiritual teachers who always help and assist the learning process. Also, the elderly become more mature in accepting their existence to prioritize God's prioritize closeness without forget to keep socializing with others. The wishes are elderly feel comfortable for the rest of their lives and can face death in husnul khotimah conditions.